Quel statut pour l’écrit en l’absence de langage oral? De l’écrit à la langue des signes - Vinter, Shirley (My University, 2000)
We propose to show a case study,of a child with a severe deafness and serious troubles of aphasic type. Until the age of 7, written language was her only means of communicating, then there was a progressive transfer from written to sign language. Presently 16 and a half years old, communicating by sign language is still rudimentary, in production as well in comprehension; she uses written language when there are difficulties of communication. This case study raises numerous questions.